Children’s breakfast habit related to their perception towards parent’s breakfast habits (study in Sedayu District, Bantul Regency)* - Winda Irwanti; Yhona Paratmanitya (Alma Ata University Press, 2016)
ABSTRACTBackground: Breakfast plays an important role in ensuring the good health and wellbeing of an individual, especially children. Evidence suggests that breakfast consumption may improve cognitive function related to memory, exam test score and the level of school attendance.Objectives: To determine the breakfast habits and its risk factors in elementary school children in Bantul.Methods: This cross-sectional study was conducted in four elementary schools in the District Sedayu, Bantul with 126 children as subjects. Breakfast habits investigated by interviews to the children.Results: This study showed that there were 33% of children had no breakfast daily, or had skipped breakfast at least once in a week. The major reasons of children skipping breakfast were not having enough time (38.1%), not hungry (30.9%) and no food available in the morning at home (16.7%). A total of 15.9% mothers and 23% fathers were not breakfast daily according to their children. Breakfast habits of children significantly associated with the children’s perception towards parent’s breakfast habits.Conclusions: Breakfast habits of children significantly associated with the children’s perception towards parent’s breakfast habits.KEYWORDS: breakfast habit, children perception, parent’s breakfast habitABSTRAKLatar belakang: Sarapan memiliki peran dalam menjaga kesehatan dan kebahagiaan seseorang, termasuk anak. Penelitian terdahulu membuktikan bahwa sarapan mampu meningkatkan fungsi kognitif yang berhubungan dengan kemampuan mengingat, nilai ujian, dan tingkat kehadiran di sekolah.Tujuan: Untuk mengetahui kebiasaan sarapan anak sekolah dasar di Kabupaten Bantul, dan faktor-faktor yang mempengaruhinya.Metode: Studi cross-sectional ini dilaksanakan di 4 sekolah dasar di Wilayah Kecamatan Sedayu, Kabupaten Bantul, dengan jumlah subjek sebanyak 126 anak. Kebiasaan sarapan diketahui dari wawancara dengan anak.Hasil: Hasil menunjukkan bahwa sebesar 33% anak sarapan tidak setiap hari, atau dalam seminggu paling tidak 1x melewatkan sarapan. Alasan utama anak melewatkan sarapan adalah tidak punya cukup waktu (38,1%), tidak lapar (30,9%), dan tidak tersedianya sarapan di rumah pada pagi hari (16,7%). Sebanyak 15,9% ibu, dan 23% ayah juga sarapan tidak setiap hari menurut persepsi anak. Kebiasaan sarapan anak berhubungan secara signifikan dengan persepsi anak terhadap kebiasaan sarapan orang tuanya.Kesimpulan: Kebiasaan sarapan anak berhubungan secara signifikan dengan persepsi anak terhadap kebiasaan sarapan orang tuanya.KATA KUNCI: kebiasaan sarapan, persepsi anak, kebiasaan sarapan orang tua